Life history of Synchytrium species parasitic on Cucurbitaceae - M. S. PAVGI, N. N. RAGHAVENDRA RAO* and (Indian Phytopathology, 2002)
Details of ontogenic development of two species of Synchytrium viz.. S. iagenariae and S. trichosanthidis parasitic on cucurbitaceous hosts revealed the two species to be alike in development of prosorus. Resting spores and their germination. The initial cell or thallus in the two species functions as prosorus, germinating at maturity by forming an attached superficial sorus of sporangia. The diploid zygote infect epidermal cells to form resting spores which germinate by forming an attached superficial sorus of sporangia. The two species exhibit a clear cut alternation of generation between haploid and diploid phases.